ANALYZING PUBLIC TRANSPORTATION ACCESSIBILITY THROUGH INTERACTIVE WEB MAPS - Murodilov , Kh. T.; Yo‘ldoshaliyev , A.S. (Educational Research in Universal Sciences, 2023)
This article explores the use of interactive web maps for analyzing public transportation accessibility. By incorporating multiple layers of data, these maps can provide a more complete picture of transportation service in a given area, helping policymakers and transportation providers identify areas where improvements are needed. The article highlights the success of the Transit Accessibility Project in the Minneapolis-St. Paul metropolitan area and emphasizes the potential of interactive web maps to promote a more sustainable and equitable transportation system.